Figurative Language in Little Mix Album Glory Days: Semantics Study - Masri Adelina P. Tarigan; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The title of this research is "figurative language in little mix album glory days” the purpose of this study is to find out what the function of figurative language and to find out the various figurative meanings contained in the lyrics of the album Glory Days. This study used a qualitative method. From the data found there are figurative connections (euphemism: data 1, inverse: data 2 and data 3), opposition (hyperbole: data 8, litotes: data 10), comparison (simile: data 4, metaphor: data 5, personification: data 6 and data 7), and repetition (anactaclasis: data 10), as also find effective meaning(data 2, data 8, data10), connotative meaning(data 4 and data 6), conceptual/denotative(data 2, data 3, data 9), and collective meaning(data 6 and data 7). This album uses dance-pop and tropical house, and the lyrics tell about love, female empowerment, and heartbreak.